2014
DOI: 10.1136/bcr-2014-207647
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis presenting as typical split hand syndrome

Abstract: DESCRIPTIONA 38-year-old man presented to a hospital with weakness of both hands (right>left) with associated generalised weakness for the past 2 years. The patient initially noticed weakness and thinning of his right hand followed by the left for 2 years, then he noticed a thinning of the arms, right more so that left, and his right thigh for the past 6 months. General examination showed flattening over the right shoulder and wasting of the thenar eminence on both hands with normal hypothenar muscles (figures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…They revealed that compound muscle action potentials (CMAP) of APB and FDI were significantly lower than CMAP of ADM. The results were presented as split hand index (SI, ) 5,6 .They found that the “split hand” could be used to differentiate ALS from CSA 5,7 . Recently, Neil reported dissociated lower limb muscle involvement in ALS 8 .…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that compound muscle action potentials (CMAP) of APB and FDI were significantly lower than CMAP of ADM. The results were presented as split hand index (SI, ) 5,6 .They found that the “split hand” could be used to differentiate ALS from CSA 5,7 . Recently, Neil reported dissociated lower limb muscle involvement in ALS 8 .…”
Section: Introductionmentioning
confidence: 99%